Susceptibilidade à compactação de um latossolo vermelho amarelo em sistema de plantio direto - Fonseca, Raionara Dantas (Universidade Federal Rural do Semi-Árido, 2019)
The resulting impact on soil structure of mechanization in agricultural operations has been an important object of study of soil dynamics in the machine soil interaction system. Soil compaction is considered to be a result of soil and environmental degradation, resulting in several impacts to soil and plant. In the no-tillage system, compaction is caused by the traffic of agricultural machinery and implements, and the use of poorly diversified production systems can significantly reduce crop productivity, especially under conditions of low water availability, as in our region. Among the studied parameters, the pre-compaction pressure, the compression index and the structural void index of the soil are essential for estimating the compaction risks of the cultivated areas. Understanding the impact of soil cover on these parameters is essential for the development of sustainable cropping systems. The objective of this work is to evaluate the effect of soil surface cover on soil compaction as a function of the compression index (Ic) and the precompression pressure (Ppc), based on soil density (DS), soil moisture ) and structural void index (e) in a no-tillage system. The objective of this work is to evaluate the effect of soil surface cover on soil compaction as a function of the compression index (Ic) and the pre-compression pressure (Pc), based on soil density (DS), soil moisture (U) and structural void index (e) in a no-tillage system. The experiment was conducted at the Rafael Fernandes farm located in Alagoinha, Mossoró / RN, the soil of the experimental area is a dystrophic Yellow Red Latosol. The experimental area consisted of a block, using no-tillage system. The block was divided into four plots of 20 m long and 6.0 m wide, totaling 0.012 ha. Soil samples were collected in volumetric rings, in the 0 - 5 layers; 5 - 10 and 10 - 20cm, totaling 36 samples, 24 being inside the planting area and 12 at the tractor crossing line outside the cultivated area. Conducted to the UFERSA Soil Dynamics Laboratory to determine the density and soil compression using the oedometry method. The results showed that the organic matter content influenced the decrease of the soil density in the superficial layers, due to the presence of the vegetal cover left by the use of the no - tillage system. The organic matter reduced with soil depth.
Monografia
Keywords: Compactação; Densidade do solo; Umidade; Índice de vazios; Soil compaction; Soil density; Moisture; Index of voids; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA